IMPROVING STUDENTS' LANGUAGE SKILLS THROUGH GROUP LEARNING - Misnah Mannahali (LLDIKTI Wilayah X, 2023)
The study aims to find out how to improve students' language skills by using a group learning model. The development of language skills can be done with a variety of techniques, one of which is the application of group learning techniques. The province of group learning is viewed from two paradigms, namely psychological and social paradigms. In this group learning process, the teacher acts as a motivator, facilitator, mediator, and evaluator. The stages used in this group learning are the group formation stage and the presentation stage. The presentation stage includes preparation and preparation of learning units (Planungsphase), implementation stage (Durchfuehrungsphase), and summary and feedback stage (Anwendungsphase). The application of group learning techniques was carried out on 3rd semester students in the German language education study program in the Sprechfertigkeit course using the Netzwerk B1 textbook. Based on the results of the study, it shows that the group learning model can improve students' language skills.